Bacterial Diversity in Chinese Rushan Cheese From Different Geographical Origins - Xue, Jia; Yang, Yi; Wang, Zhaoxia; Guo, Yurong; Shao, Yuyu (Frontiers in Microbiology, 2018)
Rushan cheese, an essential part of the Bai culture, has been produced and consumed for centuries by the Bai people living mostly in Yunnan province of China, however, studies on the naturally-occurring microbial communities of Rushan cheese are lacking. In this study, we applied high throughput sequencing technique to analyze the microbial compositions of Rushan cheese samples from three different geographical origins (i.e., Weishan, Eryuan, and Jianchuan). The microbiota in Weishan, Eryuan and Jianchuan Rushan cheese samples were distinct in terms of taxonomic composition and abundance. Linear discriminant analysis (LDA) of effect size (LEfSe) analysis found the characteristic taxonomic species in Weishan Rushan cheese samples were Lactobacillus pentosus, Lactobacillus crusorum, Lactobacillus brevis, Leuconostoc mesenteroides, and Pediococcus pentosaceus; the representing taxonomic species in Eryuan Rushan cheese samples were Lactobacillus kefiranofaciens, Lactococcus lactis, Acetobacter pasteurianus and Moraxella osloensis; by comparison, Acinetobacter was enriched in Jianchuan Rushan cheese samples. Characterization of the microbial diversity in Rushan cheese samples from different geographical origins will contribute to the understanding of microorganisms responsible for the Rushan cheese fermentation, and enable us to develop bioresources derived from Rushan cheese in the future.